Evolution and complexity of government policies to protect the health of undocumented/illegal migrants in Thailand – the unsolved challenges - Suphanchaimat R; Putthasri W; Prakongsai P; Tangcharoensathien V (Dove Medical Press, 2017)
Rapeepong Suphanchaimat,1,2 Weerasak Putthasri,1 Phusit Prakongsai,1,3 Viroj Tangcharoensathien1 1International Health Policy Program (IHPP), The Ministry of Public Health, Nonthaburi, 2Banphai Hospital, Khon Kaen, 3Bureau of International Health (BIH), The Ministry of Public Health, Nonthaburi, Thailand Background: Of the 65 million residents in Thailand, >1.5 million are undocumented/illegal migrants from neighboring countries. Despite several policies being launched to improve access to care for these migrants, policy implementation has always faced numerous challenges. This study aimed to investigate the policy makers’ views on the challenges of implementing policies to protect the health of undocumented/illegal migrants in light of the dynamics of all of the migrant policies in Thailand. Methods: This study used a qualitative approach. Data were collected by document review, from related laws/regulations concerning migration policy over the past 40 years, and from in-depth interviews with seven key policy-level officials. Thematic analysis was applied. Results: Three critical themes emerged, namely, national security, economic necessity, and health protection. The national security discourse played a dominant role from the early 1900s up to the 1980s as Thailand attempted to defend itself from the threats of colonialism and communism. The economic boom of the 1990s created a pronounced labor shortage, which required a large migrant labor force to drive the growing economy. The first significant attempt to protect the health of migrants materialized in the early 2000s, after Thailand achieved universal health coverage. During that period, public insurance for undocumented/illegal migrants was introduced. The insurance used premium-based financing. However, the majority of migrants remained uninsured. Recently, the government attempted to overhaul the entire migrant registry system by introducing a new measure, namely the One Stop Service. In principle, the One Stop Service aimed to integrate the functions of all responsible authorities, but several challenges still remained; these included ambiguous policy messages and the slow progress of the nationality verification process. Conclusion: The root causes of the challenges in migrant health policy are incoherent policy direction and objectives across government authorities and unclear policy messages. In addition, the health sector, especially the Ministry of Public Health, has been de facto powerless and, due to its outdated bureaucracy, has lacked the capacity to keep pace with the problems regarding human mobility. Keywords: migrant, health insurance, Thailand, policy formulation, policy process